2019
DOI: 10.1002/da.22881
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating PTSD from anxiety and depression: Lessons from the ICD‐11 PTSD diagnostic criteria

Abstract: Objective: Posttraumatic stress disorder (PTSD) is frequently associated with depression and anxiety, but the nature of the relationship is unclear. By removing mood and anxiety diagnostic criteria, the 11th edition of the International Classification of Diseases (ICD-11) aims to delineate a distinct PTSD phenotype. We examined the effect of implementing ICD-11 criteria on rates of codiagnosed depression and anxiety in survivors with recent PTSD.Method: Participants were 1,061 survivors of traumatic injury adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 29 publications
2
31
1
Order By: Relevance
“…These results together with previous findings (e.g. Barbano et al, 2019;Elhai, Grubaugh, Kashdan, & Frueh, 2008) indicated that removing overlapping symptoms ICD-11 criteria could not effectively reduce comorbidity. Actually, comorbidity is the rule rather than the exception in mental illness and is widely assumed to reflect the interaction between a limited number of latent traits (Zisner & Beauchaine, 2016) or causal associations among symptoms (Garabiles, Lao, Xiong, & Hall, 2019).…”
Section: Discussionsupporting
confidence: 66%
“…These results together with previous findings (e.g. Barbano et al, 2019;Elhai, Grubaugh, Kashdan, & Frueh, 2008) indicated that removing overlapping symptoms ICD-11 criteria could not effectively reduce comorbidity. Actually, comorbidity is the rule rather than the exception in mental illness and is widely assumed to reflect the interaction between a limited number of latent traits (Zisner & Beauchaine, 2016) or causal associations among symptoms (Garabiles, Lao, Xiong, & Hall, 2019).…”
Section: Discussionsupporting
confidence: 66%
“…Our sample size at Week 9 was relatively modest and thereby likely underpowered compared to evaluation of ICD criteria in adult samples (e.g. Barbano et al, 2019), as is common in PTSD research with younger samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, females are more likely to develop PTSD than males ( Christiansen and Hansen, 2015 ). Further, PTSD is frequently associated with symptoms of anxiety and depression ( Barbano et al, 2019 ) and often co-occurs with metabolic syndrome (MetS) ( Rosenbaum et al, 2015 ; Penninx and Lange, 2018 ). MetS, a risk factor for cardiovascular disease, is characterized by obesity, high blood pressure, dyslipidemia and insulin resistance ( Alberti et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%